The Posthuman Perspectives on Futuristic Technology in Mickey 17 (2025) - Andreas; Putri Ayienda Dinanti (PT. Alahyan Publisher Sukabumi, 2026)
This research examines how futuristic technology influences human identity and ethics in the movie Mickey 17 (2025) through Robert Pepperell’s posthumanism theory. The story follows Mickey Barnes, an “Expendable,” a cloned human whose body is continuously reprinted and whose memories are digitally stored. This condition raises fundamental questions about individuality, humanity, and the value of life. The study aims to identify the futuristic technologies shown in the movie and analyze their impacts on human existence. Using a qualitative descriptive method, the analysis focuses on key scenes and dialogues, supported by books, journals, and previous research on posthumanism and science fiction. The findings reveal that technologies such as the reprinting machine, memory hard drive, bioreactor, cell bioreactor, space suit, spaceship, and translator device function as tools for human survival but also blur the line between humans and machines. These technologies generate new ethical issues, particularly for cloned characters like Mickey, who face identity loss, dehumanization, and commodification. The study concludes that Mickey 17 portrays a posthuman future in which technology strengthens human abilities but simultaneously threatens human dignity. The movie invites viewers to rethink life, individuality, and moral responsibility in a world shaped by powerful technological advancements.